Assessment of the Influence and Impact of Video Analysis on Students’ Understanding of Graphs in Kinematics: A Low-Cost and Easy-to-Implement Alternative - Rosas Echevarría, Cesar Wilfredo (2020)
This study demonstrates the benefits of implementing video analysis (VA) in physics instruction. It aims at demonstrating that the implementation of VA, in addition to being a low-cost and easy-to-use technique, significantly improves students’ understanding level of graphs in kinematics (ULGK). The study compares the results obtained after applying the Test of Understanding Graphs in Kinematics (TUG-K) on a practical kinematics class in a traditional lecture against one conducted using VA, in order to evaluate the influence of VA on students’ ULGK. The population was comprised of 60 students, 30 per group, from the School of Engineering of the Universidad de Huánuco. The results show that a strong, highly significant point-biserial correlation (rpb = 0.809) (p < 0.0001) exists between these two variables, that VA has an average impact on the ULGK (Hake = 32.5%) and that the ULGK is significantly higher (p < 0.0001) when VA is applied compared to traditional instruction.